Factors affecting the semen quality of breeding bulls - Tohura, S; Parvin, A; Siddique, AB; Assaduzzaman, M; Zohara, BF; Islam, MF (Bangladesh Veterinarian, 2019)
This study aimed to investigate the effects of breed, age, scrotal circumference, Body Condition Score (BCS), season and nutrition on bull semen quality at breeding bull station of Ejab Alliance Limited, Thakurgaon, Bangladesh. A total of 777 ejaculates were collected from 25 bulls (Holstein-Friesian-10; Sahiwal-15). All semen parameters were significantly (P<0.05) higher in Sahiwal bulls than in Holstein-Friesian. The volume, individual motility, mass activity and sperm morphology were significantly (P<0.05) higher in bulls aged >3.5 - 4.5 years than in younger (2.5 - 3.5 years) and older bulls (>4.5 years). Scrotal circumference significantly (P<0.05) affected all the parameters of semen quality. The highest values were observed in bulls with scrotal circumference 31.1 - 33.0 cm and the lowest in bulls with scrotal circumference of 33.1 cm and less. The volume, individual motility, mass activity and sperm morphology were higher (P<0.05) in bulls with BCS of 4 to 4.5 than in bulls with BCS of >4.5 to 5. Significantly (P<0.05) highest values regarding semen quality were in winter and the lowest in summer. Vitamin ADE supplementation significantly (P<0.05) improved the semen quality. It is suggested that Sahiwal breeds may be reared at the bull station in the subtropical climate of Bangladesh. Semen should be collected during winter in bulls of >3.5 to 4.5 years of age with moderate scrotal circumference and BCS. The Bangladesh Veterinarian (2018) 35(1&2): 32-39